THERMODYNAMIC ASPECTS OF GASES IDEALITY - Victor Ferreira da Silva, Paulo; da Silva Lacerda Júnior, Orivaldo (Journal of Interdisciplinary Debates, 2022)
This work deals with a thermodynamic approach to the ideality of gases in a systematic and organized way. Important aspects are presented regarding the understanding of the behavior of gases and their properties, such as the properties of the physical state of matter, in which the gas is in the simplest state according to the arrangement of its molecules. It was highlighted the topics that led the scientists to arrive at the knowledge currently available, through experimental results observed by them, resulting in empirical laws that helped to understand the behavior of the gases in diverse situations, as in the cases of variations of temperature and pressure. These laws, which combined proportionately, resulted in a mathematical equation called the perfect or ideal gas equation, a law that strictly follows the formulated empirical mathematical relations and which is the starting point for the deduction of what is really the ideal or perfect gas. The gas model quoted is the basis of the kinetic theory of gases, which theory has a well-developed theoretical understanding to explain the behavior of an ideal gas. Also exposed in this work is the definition of real gases that present different behavior of the ideal gases due to the interactions that can occur between their molecules. For a better understanding of the real gases we explained ways of studying the intermolecular forces in these gases, such as the compressibility factor and the Van der Waals equation. Also, the transformations occurring in the gaseous state, such as liquefaction, are discussed. The present work was done on the basis of bibliographical research in order to have a favorable knowledge about the study of gases from the thermodynamic point of view, aiming to establish the necessary definitions of the study of the phases of matter.